2019
DOI: 10.1590/2237-6089-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of dynamic and static facial expressions of emotion among older adults with major depression

Abstract: Introduction The recognition of facial expressions of emotion is essential to living in society. However, individuals with major depression tend to interpret information considered imprecise in a negative light, which can exert a direct effect on their capacity to decode social stimuli. Objective To compare basic facial expression recognition skills during tasks with static and dynamic stimuli in older adults with and without major depression. Methods Older adults were selected through a screening process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
3
13
1
7
Order By: Relevance
“…In line with some previous findings [( 21); however, see also (20)], patients with depression recognized anger with higher accuracy compared with healthy controls. Surprisingly, we found no bias in the recognition of sadness and no deficits in the recognition of facial expression with positive valence as in previous studies (21,24). However, particularly with regard to the emotion recognition data, we need to discuss the statistical power to detect small effects (see below).…”
Section: Social Cognition In Episodic and Persistent Depressionsupporting
confidence: 47%
See 1 more Smart Citation
“…In line with some previous findings [( 21); however, see also (20)], patients with depression recognized anger with higher accuracy compared with healthy controls. Surprisingly, we found no bias in the recognition of sadness and no deficits in the recognition of facial expression with positive valence as in previous studies (21,24). However, particularly with regard to the emotion recognition data, we need to discuss the statistical power to detect small effects (see below).…”
Section: Social Cognition In Episodic and Persistent Depressionsupporting
confidence: 47%
“…Dalili et al (20) report in their meta-analysis impaired emotion recognition in patients with depression for all emotions except for sadness. Other studies indicate that depressed patients have a negative response bias or lack a positive response bias compared with healthy controls, in particular when ambiguous or neutral faces are presented [e.g., (21)(22)(23)(24)]. This bias to misinterpret faces as negative could contribute to the development and maintenance of depressive symptoms.…”
Section: Social Cognition In Episodic and Persistent Depressionmentioning
confidence: 99%
“…Furthermore, it is important to note that our findings cannot be explained by potential depression in our patient population. Indeed, as previous research has shown impaired recognition of emotional facial expressions in depressive older population, our study had excluded participants with depressive symptoms 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…본 통합적 고찰에 포함된 19편의 문헌에 대한 검토를 통 해, 각 연구자들이 측정하는 결과 변인을 정확성(Accuracy), 반응시간(Reaction Time), 민감도(Sensitivity), 강도(Intensity), 해석편향(Interpretation Bias)이라는 5가지 범 주로 분류할 수 있었다. (Leppanen et al, 2004;Ryu KH et al, 2008;Miders et al, 2010;Douglas et al, 2012;Orgeta, 2014;Zwick et al, 2017;Bomfim et al, 2019 (Surguladze et al, 2004;Csukly et al, 2009;Gollan et al, 2010;Milders et al, 2010;Bomfim et al, 2019), 이와 대조적으로 몰핑된 동적 자 극을 사용한 연구들 (Ryu KH et al, 2008;Schafer et al, 2010;Zwick et al, 2017;Bomfim et al,…”
Section: 결과 변인의 분석unclassified